Work–life balance among humanitarian aid workers - Mills, M; Visser, M; Heyse, L; Wittek, R (SAGE Publications, 2016)
A limited body of research has examined satisfaction with work–life balance of expatriate workers who live abroad, residing outside the typical “family” or “life” domain. This study aims to demonstrate how and under which organizational circumstances job autonomy can increase work–life balance satisfaction of humanitarian aid expatriates. We hypothesize that especially in humanitarian work, trust in management can buffer potential negative effects of high autonomy. We test our hypothesis by means of ordinal logistic regression, using survey data collected among expatriates of the Operational Center Amsterdam of Médecins Sans Frontières (N = 142). Results reveal that high levels of autonomy are positively related with work–life balance satisfaction when trust in the management of the organization is high. When trust in management is low, the effect of high autonomy on work–life balance satisfaction is negative. This implies that trust in management indeed buffers negative effects of high autonomy among expatriate humanitarian aid workers.